Uno più uno può fare tre, se il partito lo vuole! La Repubblica Democratica Tedesca tra Mosca e Bonn, 1971-1985 - Zamperini, Valentina (Premio Ricerca «Città di Firenze», 2014)
This work analyzes the evolution of the German Democratic Republic during 1971-1985, with particular attention to the economic sphere, relations with the Soviet Union and the Federal Republic of Germany, and the impact that changes in the international economic system have they had on these plans. The basic question concerns the actual degree of subordination of the GDR to the USSR: absolute for traditional historiography, which denies the possibility of an East German foreign policy, relative to the light of archival documents, which show a framework of bilateral relations constantly affected by tensions. In addition to analyzing the relationships in an unequal alliance between center and periphery, the study of the decision-making mechanisms internal to the GDR and the effectiveness of a system in which politics dictated the priority in terms of economic choices are at the center of this volume.